Analysis of Load-Capacity at Collapse of I-Section Thin-Walled Beam - Gawłowski, S.; Pęcherski, R.B. (Engineering Transactions, 2004)
The aim of the paper is to analyse the load-capacity at collapse for thin-walled beams under the assumption of static approach. I-section beams subjected to torsion and bending with torsion are studied. The general formula for an interaction surface was derived. The comparison of the examples solved analytically with the finite element calculations and experimental results confirms the assumed hypotheses concerning statically admissible distribution of stresses in a plastic hinge. The analysis revealed also that normal stresses have a decisive influence on the value of load-carrying capacity in the case of thin-walled beams.